Pengembangan Media Pembelajaran Berbasis Android Pada Materi Geografi Pokok Bahasan Sebaran Dan Pengelolaan Sumber Daya Alam Indonesia Di SMA Negeri 2 Limboto (Kelas XI IPS) - Daud Dos Yusuf; Fitriyane Lihawa; Rifkiansyah Rifkiansyah (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2023)
This research aims to develop Android-based learning media that can be used in learning geography at SMA Negeri 2 Limboto. The focus of this learning media is on the material of the distribution and management of Indonesia's natural resources. The development method used is the multimedia development model. This research involved students of class XI IPS as research subjects. The data collected includes data on student needs, analysis of learning materials, and evaluation of learning media that has been developed. The results showed that this Android-based learning media can increase students' interest and understanding of geography material. In addition, this learning media is also considered effective and easy to use by students. In developing this learning media, there are several components that must be considered, such as attractive interface design, relevant and interesting content, and interactive features that can increase student involvement in learning. In addition, this learning media can also be accessed offline, so students can access it anytime and anywhere. It is expected that the development of Android-based learning media can be an effective alternative in learning geography at SMA Negeri 2 Limboto.